Unity of effort requires unity of object: Why industry should not be involved in formulating public health policy - Donovan, Robert; Anwar McHenry, Julia; Vines, A. (John Wiley and Sons Ltd, 2015)
© 2014 John Wiley & Sons, Ltd. This paper provides a framework for examining the general issue of public health authorities' collaboration with industry. The framework distinguishes between industry involvement in the development of public health policy and the implementation of policy-driven interventions. A distinction is also made between industries marketing products conducive to good health versus products that impact negatively on public health (e.g. alcohol and energy-dense, nutrition-poor food and beverage industries). Drawing on concepts with respect to the effectiveness of military coalitions, it is argued that a common goal (i.e. 'unity of object') is a prerequisite for optimal co-operation (i.e. 'unity of effort') between collaborators in any sphere of activity. However, this vital precondition does not exist in the public health arena because the end goals of industry and those of public health are fundamentally different, if not opposed (i.e. profits to owners/shareholders versus the social good). It is argued that because of this fundamental disjunct between industry profit goals and the public good, unity of effort will always be compromised in any form of collaboration with industry, and particularly where public health policies and interventions are designed to negatively impact on product consumption. Hence, while industry can be asked to co-operate in implementing public health policy initiatives, industry should never be involved in developing policy initiatives.